Relationship Between Cesarean Delivery Rate and Maternal and Neonatal Mortality. Issue 4 (April 2016) - Molina, George; Weiser, Thomas G.; Lipsitz, Stuart R.; Esquivel, Micaela M.; Uribe-Leitz, Tarsicio; Azad, Tej; Shah, Neel; Semrau, Katherine; Berry, William R.; Gawande, Atul A.; Haynes, Alex B.
Abstract : Obstet Gynecol Surv 2016;71(4):201–202 Cesarean deliveries are lifesaving for obstructed labor and other emergency obstetrical conditions.